Physical-chemical properties of 5-(3-fluorophenyl)-4-amino-1,2,4-triazole-3-thiol s-derivatives - O. A. Bihdan; V. V. Parchenko (Aktualʹnì Pitannâ Farmacevtičnoï ì Medičnoï Nauki ta Praktiki)
Introduction. Currently an attempt to combine 1,2,4-triazole heterocycle with various pharmacologically active fragments of other organic molecules is popular among the scientists. Earlier we have noted that the introduction of fluorophenyl radical in the 1,2,4-triazole structure leads to the formation of compounds with new properties and it stimulates and inspires scientists for further search of new compounds among 1,2,4-triazole-3-thiol fluorphenylderivatives.